Effects of Platinum and Palladium Metals on Ni/Mg1-xZrxO Catalysts in the CO2 Reforming of Methane - Faris Jasim Abdulridha Al-Doghachi (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Nickel, palladium, and platinum catalysts (1 wt.% each) supported on MgO and MgZrO to prepare Pt,Pd,Ni/Mg1-xZrxO catalysts (where x = 0, 0.03, 0.07, and 0.15), were synthesized by using co-precipitation method with K2CO3 as the precipitant. X-ray diffraction (XRD), X-ray fluorescence (XRF), X-ray photoelectron spectroscopy (XPS), Brunauer–Emmett–Teller (BET), transmission electron microscopy (TEM), H2-temperature programmed reduction (H2-TPR), and thermo gravimetric analysis (TGA) were employed to observe the characteristics of the prepared catalysts. The Pt,Pd,Ni/Mg0.85Zr0.15O showed the best activity in dry reforming of methane (DRM) with 99 % and 91 % for CO2 and CH4 conversions, respectively and 1.28 for H2/CO ratio at temperature 900 °C and 1:1 of CH4:CO2 ratio. The stability of Pt,Pd,Ni/Mg0.85Zr0.15O catalyst in the presence and absence of low stream 1.25 % oxygen was investigated. Carbon formation and amount in spent catalysts were examined by TEM and TGA in the presence of stream oxygen. The results showed that the amount of carbon was suppressed and negligible coke formation (less than 3 %) was observed. Several effects were observed with ZrO2 use as a promoter in the catalyst. Firstly, the magnesia cubic phase stabilized. Secondly, thermal stability and support for basicity increased. Thirdly, carbon deposition and the reducibility of Ni2+, Pd2+, and Pt2+ ions decreased.